COVID-19, mental health and psychological first aid. (14th December 2020) - Minihan, E.; Gavin, B.; Kelly, B. D.; McNicholas, F.
Abstract : Crises such as the global pandemic of COVID-19 (coronavirus) elicit a range of responses from individuals and societies adversely affecting physical and emotional well-being. This article provides an overview of factors elicited in response to COVID-19 and their impact on immunity, physical health, mental health and well-being. Certain groups, such as individuals with mental illness, are especially vulnerable, so it is important to maximise the supports available to this population and their families during the pandemic. More broadly, the World Health Organization recommends 'Psychological First Aid' as a useful technique that can help many people in a time of crisis.